2001
DOI: 10.1152/ajpcell.2001.281.4.c1336
|View full text |Cite
|
Sign up to set email alerts
|

All human Na+-K+-ATPase α-subunit isoforms have a similar affinity for cardiac glycosides

Abstract: Three alpha-subunit isoforms of the sodium pump, which is the receptor for cardiac glycosides, are expressed in human heart. The aim of this study was to determine whether these isoforms have distinct affinities for the cardiac glycoside ouabain. Equilibrium ouabain binding to membranes from a panel of different human tissues and cell lines derived from human tissues was compared by an F statistic to determine whether a single population of binding sites or two populations of sites with different affinities wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
54
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 23 publications
8
54
0
Order By: Relevance
“…Normal kidney expresses predominantly one isozyme of the Na,KATPase, composed of ␣1 and ␤1 isoforms (3,4). In our study, the K i for the more resistant Na,K-ATPase component that was observed in both the NHK and ADPKD cells is consistent with the ouabain kinetics that correspond to the ␣1␤1 isozyme (37). The high ouabain-sensitive Na,K-ATPase that is unique to the cystic cells suggested the presence of additional ␣ or ␤ isoforms.…”
Section: Nak-atpase Isoform Expression In Nhk and Adpkd Cellssupporting
confidence: 84%
See 1 more Smart Citation
“…Normal kidney expresses predominantly one isozyme of the Na,KATPase, composed of ␣1 and ␤1 isoforms (3,4). In our study, the K i for the more resistant Na,K-ATPase component that was observed in both the NHK and ADPKD cells is consistent with the ouabain kinetics that correspond to the ␣1␤1 isozyme (37). The high ouabain-sensitive Na,K-ATPase that is unique to the cystic cells suggested the presence of additional ␣ or ␤ isoforms.…”
Section: Nak-atpase Isoform Expression In Nhk and Adpkd Cellssupporting
confidence: 84%
“…For this, dose-response curves for the inhibition of Na,K-ATPase activity by ouabain were determined ( Figure 7). NHK cells exhibited a monophasic ouabain inhibition profile ( Figure 7A), with a ouabain K i of 0.48 Ϯ 0.05 ϫ 10 Ϫ6 M, consistent with what has been described in normal kidney (3,4,37). In contrast, ADPKD cells showed a heterogeneous response, with two Na,K-ATPase populations with different affinities for ouabain.…”
Section: Ouabain Sensitivity Of Nak-atpase In Nhk and Adpkd Cellssupporting
confidence: 83%
“…In humans, unlike rodents, the Na,K-ATPase ␣1 isoform is sensitive to cardiac glycosides (28,29). Thus, the cardiac glycoside binding site of the ␣1 isoform may play a biological role in hypertension similar to that of the ␣2 isoform.…”
Section: Acth-induced Hypertension Depends On the Reverse Mode Of Thementioning
confidence: 99%
“…Because the ␣1 isoform is ouabainresistant in mice, it is unlikely that it is a receptor for such ligands. However, in humans the ␣1 isoform is sensitive to cardiac glycosides and may be responsive to a naturally occurring ligand (28,29).…”
mentioning
confidence: 99%
“…It is quite clear that inhibition of either the ␣1 or ␣2 isoform enhances cardiac contraction. This is of importance as human hearts express essentially equal amounts of three ␣ isoforms (␣1, ␣2, and ␣3), which are all sensitive to ouabain (10,28). Thus, in patients with congestive heart failure, inhibition of the ␣1 isoform along with the ␣2 isoform by cardiac glycosides will contribute to increased heart contraction.…”
Section: Fig 5 Kb-r7943 Abolishes Ouabain-induced Positive Cardiac mentioning
confidence: 99%